Elizabeth Barrett Browning’s Perception, Feeling and Thought of Love, and Early Married Life in "Sonnets from the Portuguese" - Ainul Karomah (Lexicon, 2012)
The objectives of this research are to discover Elizabeth Barrett Browning’s perception, feelings, and thoughts of love and to observe her early married life with her husband as depicted in her Sonnets from the Portuguese. The expressive theory is used to find the perception, feeling, and thought of the author depicted in it. The primary data or the main object of the research is the literary work itself.The results of this research show that the perceptions of love are the products ofElizabeth’s expressive act in conceiving the love itself with deep understanding which involves the realization of position and respect of her lover and herself. However, her ideas of love are defeated by her emotion of love. Moreover, she is encouraged by the power of love to make consideration in her life to choose her own course of life that she surrenders her life to her lover by agreeing to marry Robert Browning which shows her greatest expressive act of love. Thus, love has given her the opportunity to gain happiness in her life time.